Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XVII: New reports on Chinese Homogryllacris - Zhang, Qianwen; Liu, Mingyu; Bian, Xun (Zootaxa, 2023)
Based on new collections, we described one new species from Yunnan Province, i.e. Homogryllacris xishanensis sp. nov. (Chinese name: 西山同蟋螽). Meanwhile, we first describe and illustrate the male sex of Homogryllacris biloba (Bey-Bienko, 1957). After the study, these species of Homogryllacris with reduced wings could be formed into one morphological group for classical taxonomy, but they with other species of the genus (with long wings) actually lost and regained wings during evolution.